Utilizing Resources and Reducing Emissions through Waste-to-Energy Technologies in Food Processing in the Southeast Asian Agricultural Industry - Pardin Lasaksi (West Science Interdisciplinary Studies, 2023)
The application of waste-to-energy (WTE) technology in Southeast Asian food processing is examined in this study, with an emphasis on emissions reduction and better resource usage. To evaluate the social, environmental, and economic effects, quantitative evaluations were carried out at a few chosen facilities. The findings show that there has been a 60% decrease in greenhouse gas emissions, a 25% gain in energy efficiency, and a 40% reduction in the production of organic waste on a daily basis. Positive returns on an initial investment of $5 million on average, together with the creation of 200 jobs per facility, are indicators of economic feasibility. The research highlights the revolutionary possibilities of WTE technology and offers practical suggestions for the area's sustainable growth.